Building a Good Institution - Chandra, Ashoka (Journal of Engineering Education Transformations, 2006)
This is a concern that many educationists, planners and promoters have struggled with, as they endeavour to set up a truly good institution. I tend to believe that very few persons would deliberately set out to build a bad institution. They all express the wish to set up a good institution, sometimes even an outstanding institution. But this dream fails for a variety of reasons.